Designing and understanding light-harvesting devices with machine learning - Florian Häse (Nature Portfolio, 2020)
Photon-induced charge separation phenomena are at the heart of light-harvesting applications but challenging to be described by quantum mechanical models. Here the authors illustrate the potential of machine-learning approaches towards understanding the fundamental processes governing electronic excitations.